Donut‐Shaped Stretchable Kirigami: Enabling Electronics to Integrate with the Deformable Muscle. Issue 23 (7th November 2019) - Morikawa, Yusuke; Yamagiwa, Shota; Sawahata, Hirohito; Numano, Rika; Koida, Kowa; Kawano, Takeshi
Abstract: Electronic devices used to record biological signals are important in neuroscience, brain–machine interfaces, and medical applications. Placing electronic devices below the skin surface and recording the muscle offers accurate and robust electromyography (EMG) recordings. The device stretchability and flexibility must be similar to the tissues to achieve an intimate integration of the electronic device with the biological tissues. However, conventional elastomer‐based EMG electrodes have a Young's modulus that is ≈20 times higher than that of muscle. In addition, these stretchable devices also have an issue of displacement on the tissue surface, thereby causing some challenges during accurate and robust EMG signal recordings. In general, devices with kirigami design solve the issue of the high Young's modulus of conventional EMG devices. In this study, donut‐shaped kirigami bioprobes are proposed to reduce the device displacement on the muscle surface. The fabricated devices are tested on an expanding balloon and they show no significant device (microelectrode) displacement. As the package, the fabricated device is embedded in a dissolvable material‐based scaffold for easy‐to‐use stretchable kirigami device in an animal experiment. Finally, the EMG signal recording capability and stability using the fabricated kirigami device is confirmed in in vivo experiments without significant device displacements. Abstract : Stretchable electronics are significantly used to integrate electronic devices with soft biological tissues. However, conventional stretchable devices have limited applications because of the higher Young's modulus and instability in wet environments. In this study, a proposed donut‐shaped‐kirigami device envelopes the muscle, which is unaffected by the muscle deformation and thus achieves robust electromyography signal recordings.